Measuring the Welfare Level of Local Comunnity Who Take Sustainable Business Financing Based on Local Wisdom In the Islamic Microfinance Institution - Syaparuddin Razak (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2019)
This study is a single instrumental case study, the study that describes the welfare level of local community who take a sustainable business financing based on local wisdom in BMT As'adiyah Sengkang. The data was collected by questionnaires and interviews as research instruments. The data obtained from the questionnaires was analyzed by a combination of the Keynes and Khan consumption equations. Findings from the questionnaires data were verified and explored with interview data. The results are (1) APC value MPC value on physical consumption and other worship consumption of respondents for all their income levels. (2) APC and MPC values on the zakat maal payments of respondents for all their income levels are the same, constant, and (3) E1 value E2 value on the principal consumption of respondents for all their income levels. It means that the sustainable business financing based on local wisdom in BMT As'adiyah Sengkang can improve the local community welfare. So that it also contributes greatly to increasing regional GDP.